Urine antibiotic activity in patients presenting to hospitals in Laos: implications for worsening antibiotic resistance. - Khennavong, M; Davone, V; Vongsouvath, M; Phetsouvanh, R; Silisouk, J; Rattana, O; Mayxay, M; Castonguay-Vanier, J; Moore, C; Strobel, M; Newton, P (2011)
Widespread use of antibiotics may be important in the spread of antimicrobial resistance. We estimated the proportion of Lao in- and outpatients who had taken antibiotics before medical consultation by detecting antibiotic activity in their urine added to lawns of Bacillus stearothermophilus, Escherichia coli, and Streptococcus pyogenes. In the retrospective (N = 2,058) and prospective studies (N = 1,153), 49.7% (95% confidence interval [CI] = 47.4-52.0) and 36.2% (95% CI = 33.4-38.9), respectively, of Vientiane patients had urinary antibiotic activity detected. The highest frequency of estimated antibiotic pre-treatment was found in patients recruited with suspected central nervous system infections and community-acquired septicemia (both 56.8%). In Vientiane, children had a higher frequency of estimated antibiotic pre-treatment than adults (60.0% versus 46.5%; P < 0.001). Antibiotic use based on patients histories was significantly less frequent than when estimated from urinary antibiotic activity (P < 0.0001).